Use of Fiber Cracking Technology to Improve the Nutritive Quality of Corn and Sugarcane By-products for Ruminant Feeds - Dewi, Sari P.; Ridla, Muhammad; Laconi, Erika B.; Jayanegara, Anuraga (Pakistan Journal of Nutrition, 2018)
Background and Objective: Both corn and sugarcane by-products have high fiber content but low nutritive quality, which leads to decreased livestock productivity. This study aimed to evaluate the use of fiber cracking technology (FCT) to improve the nutritive quality of corn and sugarcane by-products. Feeds used in this experiment included corn straw, corn husks, corn cobs, sugarcane tops and bagasse. Materials and Methods: The feeds were combined with 5% urea and added to the FCT operated at a temperature of 135°C and a pressure of 2.30 atm for 2.5 h. The treatments tested in this study included the following: T1 (untreated corn straw), T2 (corn straw+FCT+5% urea), T3 (untreated corn husk), T4 (corn husk+FCT+5% urea), T5 (untreated corn cob), T6 (corn cob+FCT+5% urea), T7 (untreated sugarcane top), T8 (sugarcane top+FCT+5% urea), T9 (untreated bagasse) and T10 (bagasse+FCT+5% urea), with each one replicated 4 times. A Van Soest analysis was performed to determine the fiber fraction and in vitro analysis was used to measure the digestibility. Scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) were performed to confirm the decrease in the fiber fraction in the samples. Results: The FCT+5% urea treatment decreased the fiber fraction (NDF, ADF, cellulose and lignin) content of corn and sugarcane by-products. Through SEM, XRD and FTIR analysis, it was shown that the FCT+5% urea treatment destroyed the cell wall structure, decreased the cellulose crystallinity index and broke down the fiber fraction bonds. In addition, the treatment generally increased the IVDMD, IVOMD and ruminal ammonia concentration (p